Español - Español; Español; Español, (Ars Pharmaceutica (Internet), 1976)
Desintegration and dissolution "in vitro" studies have been effected about 14 tablets samples which enclose Prednisolone giving special attention at the dissolution assay for being considered more significative. All the samples show acceptable values althought differences ave acknowledged among their particulary referring to dissolution. After determining the possible correlation between the dissolution parameter T50 and desintegration total time, the existence of 12 of the studied sampIes are verified.